The Role of E-Learning in Improving Teaching and Learning Interactions in Higher Education - Yuni Bachtiar (Generasi Sains Indonesia, 2025)
This study aims to explore the role of e-learning in enhancing teaching and learning interactions in higher education. Using a qualitative approach, data were collected through in-depth interviews with lecturers and students, online classroom observations, and analysis of learning documents. The results indicate that e-learning increases learning flexibility, lecturer engagement, and the use of interactive media, which overall enhances the quality of interaction and student cognitive engagement. Although interaction between students is still limited, the implementation of pedagogical strategies that support collaboration and social communication can optimize the online learning experience. These findings confirm that the success of e-learning depends on the combination of technology, teaching strategies, and student motivation, making e-learning an effective pedagogical transformation in the digital era.